Design of impulse jet generators based on structural synthesis - Гулин, Валерий Валентинович; Устименко, Татьяна Алексеевна (Eastern-European Journal of Enterprise Technologies, 2014)
Experience in designing devices that generate impulse jets, mainly for the mining industry for working thin coal seams, well-boring, formation of stables allows to perform some generalizations, create a block diagram with its sufficiently detailed description. Basic elements of this diagram are systemized and have a mathematical description. In order to combine the elements into a system, the connection equation is developed. A mathematical model of the system is the motion equation of masses (pistons, valves, plungers, distributor components, etc.), the wave equation of unsteady flow in the connecting lines, the ratios for variable hydraulic resistances and equation of the pressure ratio in the connected hydraulic chambers of the system. Based on the mathematical model, the simulation model, reflecting the main hydrodynamic processes in all the system elements was developed. In order to verify its adequacy, a bench experiment is held, and comparison of the data obtained is performed. The comparison was carried out by both time indices of the workflow (depending on pressures in the characteristic points of time), and basic integral indicators - equivalent pressure in the impulse, impulse repetition rate, system efficiency. Analysis of the results has shown that the prediction error of the workflow using the mathematical model is in the range of from 10 % to 15.4 %, which is acceptable for engineering studies. The data obtained allow to use the block diagram, schematic diagrams of a set of possible elements, its components and their mathematical description for the system of computer-aided design of impulse jet generators. This is the basis for selecting the optimum and rational parameters when creating new diagrams for different applications of impulse jets.